Akselerasi Digitalisasi sebagai Kunci Efisiensi dan Integrasi Ekonomi Provinsi Lampung - Suryani (Business Perspective Journal, 2025)
Digitalization has become a crucial driver for improving efficiency and strengthening regional economic integration. This study aims to examine the role of accelerated digital adoption in enhancing public service effectiveness, improving business productivity, and fostering economic integration in Lampung Province. Using the theoretical frameworks of Digital Transformation, Digital Economy, and Diffusion of Innovation, this research evaluates how Lampung’s digital ecosystem contributes to creating economic value and reducing transaction costs. The results indicate that digitalization significantly improves administrative efficiency, supply chain connectivity, and access to economic services. However, its success is strongly influenced by infrastructure readiness, human resource capability, and regional government policy support. These findings affirm that digitalization is not merely a tool but a foundational element for strengthening Lampung’s economic integration and regional competitiveness. Keywords: digitalization, economic efficiency, regional economic integration, digital transformation, innovation diffusion, digital ecosystem, Lampung province